Animal Models in Periodontology: A Review - Abdul Naeem; Vinita Boloor; K S Rajesh; Shashikanth Hegde; Anupama Rao (Journal of Multidisciplinary Dental Research)
In periodontal research, animal studies are complementary to in vitro experiments prior to testing new treatments. Animal models should make possible the validation of hypotheses and prove the safety and efficacy of new regenerating approaches using biomaterials, growth factors or stem cells. Rats, hamsters, rabbits, ferrets, dogs, and primates are just a few of the many kinds of animals that have been utilised as models for human periodontal illnesses and therapies. However, animal anatomy and physiopathology differ from those of humans, making it challenging to assess novel treatments. Major periodontal diseases (gingivitis and periodontitis), their development, and innovative surgical procedures have all been studied using experimental models. This review's objective is to draw attention to the animal models that are available for dentistry research. Keywords: Periodontal disease, Animal models, Biomaterials, Periodontal surgery